Distance Learning During the COVID-19 Lockdown and Self-Assessed Competency Development Among Radiology Residents in China: Cross-Sectional Survey - Peicheng Wang; Ziye Wu; Jingfeng Zhang; Yanrong He; Maoqing Jiang; Jianjun Zheng; Zhenchang Wang; Zhenghan Yang; Yanhua Chen; Jiming Zhu (JMIR Medical Education)
Abstract BackgroundDuring the COVID-19 lockdown, it was difficult for residency training programs to conduct on-site, hands-on training. Distance learning, as an alternative to in-person training, could serve as a viable option during this challenging period, but few studies have assessed its role. ObjectiveThis study aims to investigate the impact of distance learning during the lockdown on residents’ self-assessed competency development and to explore the moderating effect of poor mental health on the associations. It is hypothesized that radiology residents who were trained through distance learning during the lockdown were more likely to report higher self-assessed competency compared to those who did not receive organized, formal training. MethodsA cross-sectional survey was conducted in 2021 among all of the radiology residents in 407 radiology residency programs across 31 provinces of China. To estimate the long-term outcomes of radiology residents’ training after the initial COVID-19 outbreak, this study measured 6 core competencies developed by the US Accreditation Council for Graduate Medical Education reported by radiology residents. Multiple linear regression and moderating effect analysis were conducted to examine the associations between distance learning, mental health status, and self-assessed competencies. Mental health status moderated the association between distance learning and self-assessed competency of radiology residents. ResultsA total of 2381 radiology residents (29.7% of the 8,008 nationwide) met the inclusion criteria and were included in the analysis. Among them, 71.4% (n=1699) received distance learning during the COVID-19 lockdown, and 73.2% (n=1742) reported mental health struggles ranging in severity from slight to extremely severe. Radiology residents who were trained through distance learning (β=0.35, 90% CI 0.24‐0.45) were more likely to report higher self-assessed competencies. This was particularly true for the competency of “interpersonal and communication skills” (β=0.55, 90% CI 0.39‐0.70). Whereas, the competency of “patient care and technical skills” (β=0.14, 90% CI 0.01‐0.26) benefited the least from distance learning. Poor mental health significantly moderated the relationship between distance learning and competency (β=−0.15, 90% CI −0.27 to −0.02). ConclusionsDistance learning, a means of promoting enabling environments during the COVID-19 lockdown, serves its purpose and helps generally improve residents’ self-assessed competencies, though different competency domains benefit unequally. The impact of mental health status calls for special attention so that distance learning can fulfill its potential.